2014
DOI: 10.1371/journal.pone.0087811
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba polyphaga mimivirus Stability in Environmental and Clinical Substrates: Implications for Virus Detection and Isolation

Abstract: Viruses are extremely diverse and abundant and are present in countless environments. Giant viruses of the Megavirales order have emerged as a fascinating research topic for virologists around the world. As evidence of their ubiquity and ecological impact, mimiviruses have been found in multiple environmental samples. However, isolation of these viruses from environmental samples is inefficient, mainly due to methodological limitations and lack of information regarding the interactions between viruses and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Interestingly, C. lausannensis presents a high resistance to selected inactivation treatments, including ethanol and hydrogen peroxide. It has been reported that other amoeba‐infecting viruses such as Acanthamoeba polyphaga mimivirus (APMV) are able to survive in various environmental and clinical substrates (Dornas et al ., ). This could become a concern since it has also been suggested that APMV as well as other amoebae‐infecting viruses that belong to Marseilleviridae could be associated with human infections (La Scola, ; Aherfi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, C. lausannensis presents a high resistance to selected inactivation treatments, including ethanol and hydrogen peroxide. It has been reported that other amoeba‐infecting viruses such as Acanthamoeba polyphaga mimivirus (APMV) are able to survive in various environmental and clinical substrates (Dornas et al ., ). This could become a concern since it has also been suggested that APMV as well as other amoebae‐infecting viruses that belong to Marseilleviridae could be associated with human infections (La Scola, ; Aherfi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Acanthamoeba castellanii were infected at an m.o.i. of 0.01 for 36 hours and then fixed with 2.5 % glutaraldehyde (Merck, Germany) for one hour before visualization by electron microscopy, ultrathin sections were prepared and analyzed at the Centro de Microscopia, UFMG, Brazil [10]. Images of our samples revealed the presence of typical mimiviruslike particles, with sizes ranging between 500 and 700 nm ( Fig.…”
mentioning
confidence: 99%
“…1A and Table 1. In order to increase the efficiency of virus recovery, samples were subjected to an enrichment process [10]. After this procedure, total DNA was extracted from the samples by the phenol-chloroform method and used as template for real-time PCR assays targeting the conserved helicase gene (primers: 5 0 -ACCTGATCCACATCCCATAACTAAA-3 0 and 5 0 -GGCCTCATCAACAAATGGTTTCT-3 0 ), using a SYBR Green Master Mix (Applied Biosystems, USA) in 10-lL reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GV are ubiquitous (Aherfi et al, 2016b;Andrade et al, 2018) and maintain infectivity in harsh environments such as alkaline lakes , frozen permafrost (Legendre et al, 2014), 3 km deep in the ocean and dry valleys in Antarctica Kerepesi and Grolmusz, 2017). GV have retained infectivity following exposure to harsh chemicals (Campos et al, 2012), extreme pH and salinity , extreme temperatures Legendre et al, 2014), and are able to persist on hospital equipment (Campos et al, 2012;Dornas et al, 2014b). To survive such extremes, GV have developed incredible capsid stability.…”
Section: Introductionmentioning
confidence: 99%